The Existence of Tax Court in Indonesia Judicial System - SUHARTONO, Slamet; HUDA, Mokhamad Khoirul (Journal of Advanced Research in Law and Economics; Vol 10 No 1 (2019): JARLE Volume X Issue 1(39) Spring 2019, 2019)
Tax Court was organized based on Act No. 14/2002 as the implementation of judicature power authorized to solve taxation lawsuits. The existence of Tax Court, following the explanation of Article 27 subsection (1) of Act No. 48/2009, is a specific court under Administrative Court as the accused subject ( subjectum litis ) is government, and the accusing subject is civil people. In addition, the accused object ( objectum litis ) is the government’s judgment ( beschiking ) on taxes that disadvantages the civil people. The existence of Tax Court in Act No. 14/2002 does not reflect the independence and impartiality of judiciary organizations due to the authority of the Minister of Finance to provide organizational, administration, and financial counseling, and thus it is considered that Tax Court does not correspond to Article 24 subsection (1) of the Constitution 1945 requiring that ‘the judicature power is independent’. Therefore, the systematization of Tax Court based on Act No. 24/2002 is non-constitutional.